2008
DOI: 10.1007/s10350-008-9271-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Caffeine on Anorectal Manometric Findings

Abstract: Caffeine 3.5 mg/kg body weight in 200 ml of water resulted in stronger anal sphincter contractions both at basal period and during voluntary squeeze. The sensory threshold was also decreased, leading to an earlier desire to defecate. Caffeine consumption may result in an earlier desire to defecate, leading to defecation if the anal sphincter can relax voluntarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Brown et al have reported that caffeinated coffee stimulated a motor response of the distal colon in some people, and tea (caffeine content 1.5-3%) had a similar effect to coffee [ 26 ]. A study in Thailand showed that caffeine intake caused a decrease of rectal sensory threshold in the defecation desire, leading to an earlier desire to defecate [ 27 ]. Colonic microbiota disturbance was another possible reason for constipation [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al have reported that caffeinated coffee stimulated a motor response of the distal colon in some people, and tea (caffeine content 1.5-3%) had a similar effect to coffee [ 26 ]. A study in Thailand showed that caffeine intake caused a decrease of rectal sensory threshold in the defecation desire, leading to an earlier desire to defecate [ 27 ]. Colonic microbiota disturbance was another possible reason for constipation [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is a ubiquitous fatigue countermeasure [ 77 ] and often used by shift workers to optimize off-duty alertness [ 78 , 79 ]. Caffeine may increase gastrointestinal motility [ 80 ] and stimulate a motor response of the distal colon in some people [ 81 ], as well as an earlier desire to defecate [ 82 ]. Caffeine consumption was also associated with increased odds for inflammatory bowel syndromes in a recent study [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parnasa et al reported that caffeine significantly reduced the time to the first postoperative bowel movement when other chemical components were excluded [ 23 ]. Several mechanisms have been proposed: caffeine promotes postoperative gastrointestinal recovery through vasodilation [ 26 , 27 ], improvement of POI by vagus nerve stimulation [ 28 , 29 ], promoting the release of gastrin, which may cause the need for defecation shortly after ingestion [ 30 ]. Researchers believe that this laxative effect is caused by not only caffeine.…”
Section: Discussionmentioning
confidence: 99%